Ideographic modernism China, writing, media - Bush, Christopher, 1968- (New York ; Oxford : Oxford University Press, 2010)
This work analyzes the collective significance of an array of figures of Chinese writing in Euro-American literature, showing how the ideograph becomes, in the modernist era, a prism through which to imagine the world in ethnographic and in technological terms.
Description based on print version record.
Includes bibliographical references and index.
Keywords: China -- In literature; Chinese language -- Writing; Modernism (Literature)